HUBUNGAN PENGETAHUAN TENTANG PERTOLONGAN PERTAMA PADA KECELAKAAN DENGAN MOTIVASI MENOLONG PADA PENGEMUDI OJEK ONLINE DI KOTA MANADO - Langi, Sharon; Mulyadi , Mulyadi; Sembiring, Erika Emnina (Universitas Sam Ratulangi, 2024)
Background: The incidence that becomes a health problem and becomes the highest number of accidents is traffic accidents. It is proven that almost 90% of victims died or were disabled as a result of this event. Drivers as first responders must have good first aid knowledge in accidents and motivation for accident victims to mitigate these losses. Objective: this study was to identify the relationship between knowledge about accident first aid and motivation to help online motorcycle taxi drivers in Manado City.Method: This research is a quantitative research, using a correlative descriptive design with a cross-sectional approach. The sample used as many as 100 online drivers using accidental sampling. Relationship analysis using spearman rho test. Results: this study found a link between knowledge of first aid and motivation to help, being in the strength of a strong relationship.Conclusion:Researchers expect online motorcycle taxi drivers to be more active in seeking information about first aid in order to increase knowledge and recommend attending first aid training so as to increase motivation to help. Keywords: Motivation to Help; First Aid Knowledge In Accidents; Online Ojek Driver